(untitled) (Research, Society and Development, 2022)
Statistical analysis and the epidemiological situation observed in the city of Santos – SP between 2006 and 2016. To assess the spatial distribution of tuberculosis cases over the years and to correlate Tuberculosis with other epidemiological variables. Study of ecological design and temporal trend that aims to statistically evaluate 4533 cases of Tuberculosis. The analysis of the results was centered on the variables: Gender, Closure, Drug addiction and Municipalities. There was a 3% reduction in the number of cases between 2006-2016. Regarding the outcome of patients diagnosed with Tuberculosis, 72.7% of the cases were cured in the decade evaluated, 4.75% died due to Tuberculosis and 3.2% died from other causes. The treatment dropout rate was 15.2%. The neighborhoods with the highest number of cases over the ten years were: Radio Club (354), Vila Matias (257), Vila Nova (220). The municipality of Santos presented a variation in the number of annual cases over the period studied, with times of increase and decrease in the number of cases, but with stabilization in the last years evaluated.